Is the proposed distinction of gaming disorder into a predominantly online vs. offline form meaningful? Empirical evidence from a large German speaking gamer sample. (December 2021) - Montag, Christian; Schivinski, Bruno; Pontes, Halley M.
Highlights: Disordered gaming is distinguished by predominantly online, offline, and unspecific gaming. Online gamers showed the highest tendencies towards disordered gaming. Gaming via desktop computers was linked with the highest disordered gaming levels. Abstract: In the eleventh revision of the International Classification of Diseases (ICD-11), Gaming Disorder (GD) is distinguished between disordered gaming occurring predominantly online, offline, and unspecified. Currently, no study has investigated whether such a distinction is meaningful in diagnosing disordered gaming. Therefore, a large group of gamers with varied tendencies towards disordered gaming was recruited to examine this issue. A large sample (N = 2, 768) was recruited and data were collected on disordered gaming, along with information on their preferred gaming mode and device used to play. The present study shows that the distinction between online and offline gaming mode proposed by the WHO is meaningful because online gamers presented with the highest disordered gaming scores followed by mixed gamers (those stating to equally prefer online and offline gaming), and offline gamers. Finally, it was also observed that the type of device for gaming used associated with disordered gaming levels. Specifically, those reporting mostly to use their desktop computer for gaming showed the highest disordered gaming scores. The present study lends empirical support for the consideration of both gaming mode and gaming device in the study of disordered gaming.